Wheeling into School and Out of Crime: Evidence from Linking Driving Licenses to Minimum Academic Requirements - Rashmi Barua; Marian Vidal-Fernández (Institute for the Study of Labor (IZA), 2016)
Since the late 1980s, several U.S. states have set minimum academic requirements for high school students to apply for and retain their driving licenses. These laws popularly known as "No Pass No Drive" (NPND), encourage teenagers with a preference for driving to stay in school beyond the minimum dropout age. Using Federal Bureau of Investigation (FBI) arrest data, we exploit state, time and cohort variation to show that having an NPND law in place is associated with a significant decrease in arrests due to violent, drug-related and property crime among males between 16 to 18 years of age. We argue that our findings are driven by an increase in education rather than incapacitation and that NPND laws are a relatively low cost policy that generates positive externalities beyond and in addition to the minimum dropout age.
Keywords: K14; J24; J18; 330; No Pass No Drive laws; juvenile crime; education